A Dublin Magdalene Laundry Donnybrook and church-state power in Ireland - Coen, Mark; O'Donnell, Katherine 1966-; O'Rourke, Maeve (Bloomsbury Academic, 2023)
"Towards the end of the 20th century, the decades of abuse and neglect endured by those held within Ireland’s comprehensive carceral network was finally exposed. The treatment endured by people, particularly women, in these orphanages, industrial schools, psychiatric hospitals, Mother and Baby Homes and Magdalene Laundries now attracts increasing investigation and scholarship. Bringing together contributions from leading experts across a broad range of disciplines, including history, philosophy, law, archaeology, criminology, accounting and architecture, this book offers a comprehensive exploration of the Magdalene system through a close study of the Donnybrook Magdalene Laundry in Dublin. To date, the Justice for Magdalenes Research organisation has recorded the names of 314 women and girls who died at Donnybrook Magdalene Laundry. By focusing on this one institution, its ethos, development, operation and built environment, and the lives and experiences of the women held there, the book reveals the underlying framework of Ireland’s wider system of institutionalisation. This analysis includes the privatisation and commodification of public welfare, reproductive injustice, institutionalised misogyny, class prejudice, the visibility of supposedly ‘hidden’ institutions and the role of oral testimony in reconstructing history. In doing so, the authors uncover truths missing from the state’s own investigations and shed new light on how these brutal institutions came to have such a powerful presence in Irish society, and the significance of their continued impact on modern Ireland."
Bevorzugte Informationsquelle: Landingpage, da kein Titelblatt vorhanden (Bloomsbury Collections)
Keywords: Donnybrook Magdalene Laundry / History; Women / Institutional care / Ireland / Dublin / History; Children / Institutional care / Ireland / Dublin / History